Life cycle and population dynamics of Aleurolobus teucrii (Homoptera Aleyrodidae) in Eastern Sicily (Bollettino di zoologia agraria e bachicoltura, 2024)
In 1995-96, a study was carried out in Eastern Sicily on the biologyand ethology of Aleurolobus teucrii Mifsud & Palmeti, that lives on Teucriumfruticans L. (Labiatae). The whitefly has two yearly generations, with adults flyingin May-June and July-August; it overwinters in the nymphal stages, especially 3rdand 4th instars, and its development only slightly slows down during the coldestmonths. Natural mortality at pre-imaginal stages was quite modest throughout thestudy. Parasitization by Encarsia olivina (Masi) (Hymenoptera Aphelinidae) wasfrequently observed, though usually at moderate levels. Direct contro! of thewhitefly is not thought to be necessary at present, in spite of the increasingcommerciai interest in its host plant.
Keywords: Aleurolobus teucrii; biology; Encarsia olivina; Italy